2023
DOI: 10.1111/ajae.12420
|View full text |Cite
|
Sign up to set email alerts
|

Structural identification of weather impacts on crop yields: Disentangling agronomic from adaptation effects

Abstract: A large literature has assessed the impacts of climate change on agricultural production by estimating reduced‐form models of crop yields conditionally on weather and individual fixed effects. The estimates obtained are usually interpreted as the weather impacts on yields once farmers have adapted. Yet, few attempts have documented that farmers do adapt to weather, and none have verified that these adjustments actually impact crop yields. Our objective here is to unpack how weather affects agricultural product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
1
0
0
Order By: Relevance
“…The farmer recurs to this input with the sole aim of limiting further losses. These results align with the conclusion of Kumbhakar and Tsionas (2010) [39] for Spain, where the authors found that phytosanitary products are risk-reducing inputs, and for Bareille and Chakir (2021) [40] for France.…”
Section: Dependent (Y)supporting
confidence: 90%
“…The farmer recurs to this input with the sole aim of limiting further losses. These results align with the conclusion of Kumbhakar and Tsionas (2010) [39] for Spain, where the authors found that phytosanitary products are risk-reducing inputs, and for Bareille and Chakir (2021) [40] for France.…”
Section: Dependent (Y)supporting
confidence: 90%
“…Recent advances in the microeconomic foundations of statistical yield models could help address these concerns (e.g. Mérel andGammans 2021, Bareille andChakir 2024).…”
Section: Conclusion and Directions For Further Researchmentioning
confidence: 99%